KAJIAN MENGENAI REPRESENTASI VISUALISTIK DAN KEMAMPUAN MENYELESAIKAN MASALAH MATEMATIKA - Mohammad Rif'at (STKIP Melawi, 2014)
This is an experimental research design, i.e. visualistic teaching and learning with two ways design. Due to two ways asymptotic significancy and absolute extreme value obtained that visual competencies for sampel normally distributed and homogeny classified sampels, also no treatment effect among subjects. This research results explain that after the first visualistic treatment, there is no difference in visualizing problems, but significantly difference after the second and the third visualistic competencies.This research conclusions:(1) visual competencies are elements of chain of reasoning for achieving formal analytic competencies, (2) visual and analytic competency are parallel in solving mathematic problems, (3) vsual and analytic competency are not hierarchical, but in adequate relation, (4) solving visual-analytic problem always start from visual thinking, and then thinking analytically, (5) visual construction avtivities are mental process, i.e. abstraction of reflective of systematic visualization. This research come to suggest that: (1) teaching and learning mathematics show visual and algebra thinking activities, (2) mathematic content in teaching and learning show that visual competency is an integrated part of every study activity and not only developed for deeper content and formal analytic competency, but also oriented to visual analysis in developing creativity and ability thinking alternatively.Key Words: analytic, manipulative, deduction, visualistic, visual teahing and leraning, intuition, abstraction, mathematic argument, illusion, visual analogy.